Análisis técnico como herramienta para optimizar la evaluación de alternativas de inversión en la Bolsa de Valores de Lima - 2014. - Sotomayor Tirado, Neisser Alberto (2014)
This paper presents research on the application of technical analysis to market Lima Stock Exchange (BVL) where it is intended to verify and test whether technical analysis optimizes the evaluation of investment alternatives specifically the purchase or sale of shares. All this work was carried out over a period of 50 Wheels (June to August 2014) which describe and analyze the different components of Technical Analysis, verifying the importance and effectiveness with the RSI indicators and MACD to show buy signals or sale of shares and not rather predict future prices. Note that this research was based on analysis of the five shares of Selective Index Lima Stock Exchange (ISBVL) - Volcan Ferreycorp, Grana y Montero, Rio Alto Mining and Alicorp; where they could test the hypothesis, which states that if technical analysis can optimize the evaluation of alternatives for buying and selling of shares listed on the Lima Stock Exchange, showing clear signs of buying and selling in the analysis of the actions mentioned; from which we conclude that technical analysis is a valuable tool that features high efficiency and predictive power in the short term.